Raba eno- in dvojezičnih slovarjev med študenti anglistike - Kavalir, Monika (Vestnik za tuje jezike, 2010)
The study of dictionary use in 32 first-year students of English at the University of Ljubljana in the academic year 2009-2010 shows that students use a variety of dictionaries with a slight preponderance of monolingual dictionaries over bilingual ones. The bilingual dictionaries listed do not include some of the most recent and most comprehensive dictionaries while some of the most frequently used resources are quite modest sized. The students are already predominantly users of electronic and on-line dictionaries with a lower frequency of printed resources - a trend which is only likely to accelerate with the advent of new bilingual on-line dictionaries. These results have practical relevance for teachers in all sectors, from primary and secondary schools to universities, as they point towards a need for additional training in the use of bilingual dictionaries. The transition from printed to electronic and on-line resources can also be expected to induce changes in EFL methodology at all levels.
Keywords: raba slovarjev; enojezični slovarji; dvojezični slovarji; anglistika; didaktika angleščine